(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2020)
The development of technology in the digital native era causes the need for adaptation of education, one of which is cultural arts education. It is intended that the art and culture learning process can collaborate and negotiate with native digital technology to improve practical and theoretical skills in the global canon. Therefore, it is necessary to study the limitations of the art and culture learning process in the digital native era. This study also discusses and analyzes the responses of teachers, students, and parents as an ecosystem for the art and culture learning process within the limitations that occur. This research uses a mixed-methods with an interdisciplinary approach to explore educational perspectives, learning methods, technology, which is combined with the liminality conditions of the art and culture learning process in the digital native era. Collecting data using literature and documentation studies, and questionnaires via google form. The spatial boundaries of the research included 10 elementary schools, 10 junior high schools, and 10 high schools in Surabaya, East Java, which were randomly selected. The results showed that (1) the art and culture learning process by utilizing digital native technology has the potential to become sustainable education; (2) provide creative challenges for teachers in delivery, as well as for students in its use; and (3) liminality that occurs in the art and culture learning process occurs in an effort to balance and negotiate between classical and modern learning, practical models and theories, as well as between the orientation of the end result and the orientation of sustainable process outcomes.